# Trig

posted by Jill

Trig Identity.

1-sin^2x/1-cosx

1. bobpursley

Identity? Where is the equal sign?

2. Jill

It has to be solved on its own.

## Similar Questions

1. ### Trig

prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
2. ### Trig

If secx = 8 and -pi/2 < x < 0, find the exact value of sin2x Use the identity sin 2x = 2(sinx)(cosx) if secx = 8, then cosx = 1/8 where x is in the fourth quadrant. consider a right angled triangle with x=1, r=8, then y=?
3. ### Trig........

I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
4. ### math (trig)

i have some problems doing trig the first one is: Show that cos(x/2) sin(3x/2) = ½(sinx + sin2x) i know that you are supposed to substitute all those trig function things in it but i kind of forgot how to the only that i can see substituting …
5. ### Pre-Cal (verifying trig identities)

How would you verify the identity? sin^1/2x-cosx-sin^5/2xcosx=cos^3xradsinx
6. ### trig

prove the following trig identity: a) sin(pi/6 + x) + sin (pi/3 + x) + sin (pi/2 + x) = ((sqrt3) +1)/2 (sinx +(sqrt3)cosx) b) sin(pi/4 + x) + sin(pi/4 - 4)= (sqrt2)cosx
7. ### trig

Prove that the statement is an identity: (tanx/cscx)=(1/cosx)-cosx
8. ### Calculus

Use a trig identity to combine two functions into one so you can solve for x. (The solution should be valid for any value of t). 3cos(t) + 3*sqrt(3)*sin(t)=6cos(t-x) I know that 6 cos(t-x) can be 6(cos(t)cosx(x)+sin(t)sin(x)) I don't …
9. ### Precal

Verify the identity: sin^(1/2)x*cosx - sin^(5/2)*cosx = cos^3x sq root sin x I honestly have no clue how to approach the sin^(5/2)*cosx part of the equation
10. ### Precalculus/Trig

I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions